The Hidden Struggle: How the Learning Environment Influences Impostor Phenomenon in Medical Students - Susanna Gabriella Soedjianto; Daniel Ardian Soeselo; Gisella Anastasia; V Dwi Jani Juliawati; Natalia Puspadewi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: High achievers frequently suffer from the impostor phenomenon, which is typified by emotions of intellectual fraudulence and self-doubt when success is attributed to external factors, such as luck or timing, rather than actual abilities. The competitive learning environment in medicine typically demands high academic standards, which makes medical students vulnerable to this phenomenon. Aims: This study aimed to investigate the correlation between pre-clinical medical students’ experiences of the impostor phenomenon and their perceptions of the learning environment.Methods: This cross-sectional study was conducted among second- and third-year pre-clinical students from the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Total sampling was applied to students achieving grades above the cutoff. The Clance Impostor Phenomenon Scale (CIPS) and Dundee Ready Educational Environment Measure (DREEM) were used to collect data. We obtained data from 255 preclinical medical students.Results: We obtained data from 255 preclinical medical students. On average, students thought their learning environment was quite good, with an average score of 131.42 out of 200, and they frequently experienced the impostor phenomenon, which had a prevalence of 67.1%. This study also discovered that there was a significant moderate negative correlation between perception of the learning environment and the occurrence of the impostor phenomenon (r = -0.410, p < .001), as shown by the higher CIPS scores of students who felt that their learning environment was poor.Conclusion: This study emphasized that a supportive learning environment plays an important role in lowering impostor feelings among medical students. Strengthening aspects such as mentorship, constructive feedback, and peer support may help reduce psychological burden and improve students’ academic experience.